Pengaruh Persepsi Kemudahan dan Persepsi Manfaat Terhadap Minat Beli pada Konsumen Tokopedia di Jakarta - Marini Alexandra; Tinton Ramadhan (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study refers to an understanding of the effect of perceived ease of use and perceived usefulness on purchase intention in Tokopedia consumers. This research uses quantitative approach, the sampling technique used is Non Probability Sampling, the method uses purposive sampling with a sample size of 154 respondents by collecting questionnaires distributed via Google Form. Data analysis was performed using SPSS. Based on the results of the t test positive and significant perceptions of interest in repurchase related to the results of t arithmetic 6.324> t table 1.65501 and the variable perception of beneficial benefits is positive and significant on repurchase interest with the results of t arithmetic 5.287> t table 1, 65501. Besides that, the results of the trial prove with the results of the count 128.212> f table 3.06